2010
DOI: 10.1373/clinchem.2009.140707
|View full text |Cite
|
Sign up to set email alerts
|

LOX Index, a Novel Predictive Biochemical Marker for Coronary Heart Disease and Stroke

Abstract: BACKGROUND: Lectin-like oxidized LDL receptor 1 (LOX-1) is implicated in atherothrombotic diseases. Activation of LOX-1 in humans can be evaluated by use of the LOX index, obtained by multiplying the circulating concentration of LOX-1 ligands containing apolipoprotein B (LAB) times that of the soluble form of LOX-1 (sLOX-1) [LOX index ϭ LAB ϫ sLOX-1]. This study aimed to establish the prognostic value of the LOX index for coronary heart disease (CHD) and stroke in a community-based cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 38 publications
2
105
1
Order By: Relevance
“…The daily consumption of tobacco was 26±13 pieces, and the duration of smoking was 38±12 years. The mean serum sLOX-1 level in the smokers was 1.51±1.04 ng/mL, which is higher than the 0.92 ng/ mL reported in the general population in a population-based Suita cohort study 12) .…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…The daily consumption of tobacco was 26±13 pieces, and the duration of smoking was 38±12 years. The mean serum sLOX-1 level in the smokers was 1.51±1.04 ng/mL, which is higher than the 0.92 ng/ mL reported in the general population in a population-based Suita cohort study 12) .…”
Section: Discussioncontrasting
confidence: 64%
“…The sLOX-1 level has also been shown to increase in patients with coronary artery diseases in accordance with increases in inflammatory markers 7) . A cohort Suita study of a Japanese population reported that the smoking rate was higher in the group with higher serum sLOX-1 levels than in the group with lower sLOX-1 levels 12) . However, the relationships between the sLOX-1 level and various parameters in smokers are unknown.…”
Section: Correlations Between the Serum Slox-1 Levels And Clinical Pamentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, hs-CRP might be a marker of inflammation due to oxidative stress, and an association between hs-CRP and arterial wall stiffness might be observed in the present study. Thus, the association between LDL-C and CAVI including hs-CRP remains a future topic to be investigated, especially in further combination with apolipoprotein B14 or oxidized LDL-C 23) . The present study had several limitations.…”
Section: Discussionmentioning
confidence: 99%